Crime and justice : a guide to criminology - Marmo, Marinella; De Lint, Willem, 1959-; Palmer, Darren (Pyrmont, NSW : Thomson Reuters (Professional) Australia, 2012)
Fully revised and updated, this 4th edition offers a comprehensive guide in criminal justice and criminology that is well suited to a dual-semester approach. It covers a wide range of topics including: different forms of crimes - from street crime to state crime and international crimes; who commits crimes and who are the victims of crimes; and how society responds to crime. This book offers a balance between critical and administrative criminological traditions to add to the discourse of crime and justice in the twenty-first century
Previous ed.: Sydney : Lawbook Co., c2006.
Includes bibliographical references and index.
Keywords: Criminology -- Australia -- Textbooks; Criminal justice, Administration of -- Australia -- Textbooks